Ekonomi Kreatif dan Daya Tarik Objek Wisata Studi Kasus Objek Wisata Paepira Lakeside - Agnes Avenia Barus; Pitri Aulia Usman Lubis; Putri Kemala Dewi Lubis (Masyarakat Ekonomi Syariah Bogor, 2024)
This research was conducted to see an overview of the potential for creative economic development at the Paepira Lake Side tourist attraction, so that it can increase tourist attraction. The research method used was descriptive case study research. The author looked at the potential of the Paepira Lake Side tourist attraction and then analyzed it based on the following aspects. aspects of tourist attraction and creative potential. The Paepira Lake Side tourist attraction has potential but looking at the aspects of tourist attraction it can be concluded that it does not meet the criteria. Recommendations that can be given by researchers are to increase cooperation between the local community, government, business people and academics to build and develop tourism that is more interesting to visit. The economic sub-sector that can be prioritized is the culinary aspect.